Prefab Russia - Florian Urban (Docomomo Journal, 2022)
A classic view of mass housing apartments is shown on Russian television every New Year's Eve. In Eldar Ryazanov's 1975 movie lroniya sud'by (Irony of Fate), a man wakes up in what he believes to be his bedroom and suddenly finds himself surrounded by strangers. It turns out that after a vodka-soaked night and an unplanned flight on the wrong airplane he had